Evaluation of Cardiometabolic Factors Affecting Chronotropic Incompetence: A Cross-Sectional Retrospective Study in Sanglah General Hospital, Bali - Prana Jagannatha, Gusti Ngurah; Yasmin, AA Ayu Dwi Adelia; Surya Pradnyana, I Wayan Agus; Kamardi, Stanly; Wiryawan, I Nyoman; Wita, I Wayan (Jurnal Kardiologi Indonesia, 2022)
Background: Recent studies have identified that chronotropic incompetence is correlated with poor cardiometabolic health and systemic inflammation that results in exercise intolerance, impaired quality of life and death due to cardiovascular disease (CVD). Unfortunately, there’s still paucity of data regarding cardiometabolic factors associated with chronotropic incompetence. The purpose of this study was to identify the cardiometabolic factors associated with chronotropic incompetence. Methods: This study was a cross-sectional retrospective study using cardiac treadmill stress test data at Sanglah General Hospital from May 2018 - May 2020 and 136 patients were enrolled. Data analysis used SPSS version 21. Pearson chi-square test was used to compare categorical variables based on cardiometabolic risk factors in chronotropic incompetence. Results: Patients were divided based on the characteristics of age, gender, smoking status, body mass index, coronary artery disease, heart failure, hypertension, dyslipidemia, type 2 diabetes mellitus (T2DM), the levels of HbA1C, total cholesterol, LDL, HDL, and triglyceride. In this study, it was found that T2DM (PR 2.29; 95%CI 1.16–3.37), HbA1C (PR 3.13; 95%CI 2.31-4.22), dyslipidemia (PR 1.773; 95%CI 1.170–2.687), high total cholesterol (PR 2.396; 95%CI 1.650-3;481), and high LDL level (PR 1.853, 95%CI 1.229-2.794) were significantly associated with chronotropic incompetence (all p-value <0.05), while other factors were not significantly related. Conclusion: Chronotropic incompetence can impair quality of life and contribute to cardiovascular mortality. However, T2DM, high HbA1C, dyslipidemia, high total cholesterol and LDL levels were found to be associated with chronotropic incompetence. This may contribute to higher cardiovascular risk attributed to those factors.